A organização curricular dos cursos de Pedagogia e a educação infantil no município de São Paulo - Carnicero, Laura Brito (2018)
This study intends to analyze the curricular organization of the Pedagogy degrees in São Paulo city, under the critical philosophy perspective of the pseudo-formation treated by Adorno (1995). It deals with a hypothesis that, despite the recent introduction of mandatory early childhood education in basic education, this stage of education is not relevant within the curricular organizations of pedagogy degrees. It intends to identify a relevance and an incidence of the specific disciplines related to early childhood education through the analysis of the curricular organizations of the degrees. The research concludes that there are disconnections for the websites. The data demonstrate that there is low incidence of disciplines related to early childhood education in the degrees, being more frequent those related to teaching practices